Opioid Prescription Drug Use and Expenditures in US Outpatient Physician Offices: Evidence from Two Nationally Representative Surveys - Qureshi, Zaina P (Cancer Ther Oncol Int J, 2017)
BACKGROUND: Opioids are widely prescribed for their analgesic properties. Chronic opioid use is a persistent problem in the US. Nevertheless, little is known about its prescribing and utilization patterns and overall expenditures. OBJECTIVE: This study examined secular trends in opioid prescription drug utilization and expenditures, along with factors associated with opioid prescription drug use in US physician offices. METHODS: National Ambulatory Medical Care Survey (NAMCS) and Medical Expenditure Panel Survey (MEPS) data (2006–2010), both nationally representative surveys, were used to assess the trend, predictors of opioid prescription among US adults (more than 18 years) and the opioid-associated expenditures as a whole and borne by the patients in outpatient settings. RESULTS: Opioid prescription drugs use among US adults in outpatient settings, as a percentage of all prescription drugs, showed a gradual increase since 2006, leveling off in 2010. Opioid prescription drug expenditures showed an upward trend from 2009 after declining over three years. Mean out-of-pocket payments per prescription steadily declined over study period. LIMITATIONS: Cross-sectional nature and visit based information of NAMCS do not provide the actual prevalence and the reason for opioid prescription. CONCLUSIONS: Given the upward trend in opioid prescription drug utilization and associated expenditures, clinicians may benefit from evidence-based methods of monitoring prescription opioid use to prevent misuse, abuse, and other adverse patient outcomes. FUNDING: Drs. Qureshi, Haider, Ball, Horner and Bennett’s efforts are partially supported by the University of South Carolina’s ASPIRE I. Dr. Wooten’s effort is funded by the National Institute on Drug Abuse (K01DA037412).